2016
DOI: 10.1002/2015jg003069
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of polychlorinated biphenyls and organochlorine pesticides with sedimentary organic matter of retrogressive thaw slump‐affected lakes in the tundra uplands adjacent to the Mackenzie Delta, NT, Canada

Abstract: Using a comparative spatial analysis of sediment cores from eight lakes in tundra uplands adjacent to the Mackenzie Delta, NT, we examined how the presence of retrogressive thaw slumps on lake shores affected persistent organic pollutant (POPs, including polychlorinated biphenyls and organochlorine pesticides) accumulation in lake sediments. Sediments of slump‐affected lakes contained higher total organic carbon (TOC)‐normalized POP concentrations than nearby reference lakes that were unaffected by thaw slumps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The smaller pool of DOC in lakes impacted by thaw slumping would facilitate each unit of OC to scavenge a relatively greater concentration of PACs from the water column, resulting in the higher concentration of PACs per unit of sedimentary OC (MacDonald et al, 2002). A similar process was inferred as driving elevated TOC-normalized persistent organic pollutant concentrations in the same lakes, as persistent organic pollutants are also highly hydrophobic (Eickmeyer et al, 2016). The increase in OC-normalized PAC concentrations could potentially impact benthic organisms that ingest these contaminants and subsequently enter the food web and biomagnify in slump-impacted lakes.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 53%
See 2 more Smart Citations
“…The smaller pool of DOC in lakes impacted by thaw slumping would facilitate each unit of OC to scavenge a relatively greater concentration of PACs from the water column, resulting in the higher concentration of PACs per unit of sedimentary OC (MacDonald et al, 2002). A similar process was inferred as driving elevated TOC-normalized persistent organic pollutant concentrations in the same lakes, as persistent organic pollutants are also highly hydrophobic (Eickmeyer et al, 2016). The increase in OC-normalized PAC concentrations could potentially impact benthic organisms that ingest these contaminants and subsequently enter the food web and biomagnify in slump-impacted lakes.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 53%
“…Sediment cores were collected in 2006 and 2007 from a number of lakes in the region. Results of radiometric dating and core chronology development have been published previously for these same cores (Deison et al, 2012;Eickmeyer et al, 2016;Thienpont et al, 2013). Following the naming established by , lakes impacted by thaw slump activity are indicated as "b" lakes, while reference lakes, similar in size and location but lacking slump activity, are called "a" lakes.…”
Section: Core Collection and Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study involved a large-scale investigation of the temporal and spatial distributions of CUPs in surface seawater and atmosphere. Previous studies have focused mainly on CUPs at specific regions or locations (Eickmeyer et al, 2016;Li et al, 2016;Ruggirello et al, 2010;Yeo et al, 2004), with few having largescale profiles (Ma et al, 2015). Zhong, Xie, Cai, et al (2012) studied CUPs during the 4th Chinese National Arctic Research Expedition (CHINARE) in a similar region of the North Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…However, Deison et al (2012) showed that total and methyl mercury were lower in lakes with retrogressive thaw slumping, due to dilution with inorganic material, and concluded that thaw slumps were not a significant source of mercury to lakes of the Mackenzie Delta Uplands. On the other hand, polychlorinated biphenyls (PCBs), a banned class of persistent organic pollutant, as well as organochlorine pesticides were found in greater concentrations in sediment cores taken from lakes with retrogressive thaw slump activity in their catchments (Eickmeyer et al 2016). The dilution by inorganic matter was implicated by the elevated PCB concentrations observed in sediments, as these hydrophobic organic contaminants were associated with and concentrated on the smaller pool of available organic carbon in slump-impacted lakes (Eickmeyer et al 2016).…”
Section: Mackenzie Delta Uplands Northwest Territoriesmentioning
confidence: 99%